Hidden in plain sight: a field guide - Lee, Maria Yin Yin (Nanyang Technological University, 2024)
This illustrated guide book offers the reader a glimpse into the world of folklore and hidden creatures. Its concepts and written lore are inspired by themes and motifs from South East Asia; and these also serve as metaphors for navigating our modern and fast-paced world. It hopes to bring light to societal issues such as how minority groups tend to be overlooked or unseen by the general public, as well as encourages the reader to reflect on what mindfulness and being in the present moment means to them.